2017
DOI: 10.4102/sajid.v32i1.64
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of knowledge, attitude and practice of post-exposure prophylaxis against blood-borne viral infection among dental surgeons in a teaching hospital

Abstract: Background: This study was aimed at assessing the level of knowledge, attitude and practice of dental surgeons on human immunodeficiency virus (HIV) and hepatitis B virus (HBV) post-exposure prophylaxis (PEP).Methods: A descriptive, cross-sectional study was conducted among all the consenting dental surgeons at the University of Benin Teaching Hospital, Benin City, Nigeria, between May and July, 2015. The survey was carried out using a self-administered, anonymous, twenty-five item, and structured questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
1
5
2
Order By: Relevance
“…Our study shows that less than half of the students had positive knowledge regarding the length of time of PEP. This value is low compared to the results of Mathewos et al [ 17 ] and Okoh & Saheeb [ 20 ] on two different populations, healthcare workers in Ethiopia and dental surgeons in Nigeria respectively, while higher than results reached by Elsadig [ 21 ] among Sudanese dentists.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…Our study shows that less than half of the students had positive knowledge regarding the length of time of PEP. This value is low compared to the results of Mathewos et al [ 17 ] and Okoh & Saheeb [ 20 ] on two different populations, healthcare workers in Ethiopia and dental surgeons in Nigeria respectively, while higher than results reached by Elsadig [ 21 ] among Sudanese dentists.…”
Section: Discussioncontrasting
confidence: 71%
“…We found that our students had knowledge of the preferable time for taking PEP while, Okoh & Saheeb [ 20 ] reported higher percentage than our students. But our results have higher percentage than both Elsadig [ 21 ] and Kasat el al.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…There are few studies that reported on utilisation and outcome of PEP for both HIV and HBV in Africa (Ifeanyichukwu and Ofili, 2013; Okoh and Saheeb, 2017). The main objectives of this study were to examine the utilisation and outcome of PEP for both HIV and HBV in a tertiary hospital in North-Western Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…These results are similar to that of Okeke, et al[46] which shows the low level of preventive measures such as vaccinations, despite the prevalence of needle-stick injuries amongst medical students in Jos University Teaching Hospital, Nigeria. In another study on dental surgeons in the University of Benin Teaching Hospital, Nigeria, it was revealed that 64% of dental surgeons did not take PEP (Post-exposure Prophylaxis) after exposure to the risk of HIV/HBV co-infection[47]. This present study shows thatthere's an average preventive practice of HIV/HBV among Lagos residents, and these findings are similar to previous ones which show average level of precautionary techniques by hairdressers and barbers through reusing razors, non-sterilization, lack of disinfection, lack of vaccination, lack of washing hands, lack of protective gear such as gloves, amongst others [48-50].…”
mentioning
confidence: 99%